Third Ventricular Colloid Cyst - An Organic Cause of Mania: A Case Report - Penubarthi, Sravanthi; Sureshkumar, Kailash; C, Sivabackiya; Pindicura, Sundarachalam; Kailash, Shabeeba Z (Current Psychiatry Research and Reviews, 2022)
Background: Psychiatric manifestations due to space-occupying lesions, although not uncommon, are generally misdiagnosed, leading to unfavorable outcomes. A colloid cyst is a slow-growing, benign tumor in the anterior part of the third ventricle, which frequently presents with neurological complaints like headaches and gait disturbances. However, a patient with a colloid cyst may also present with OPD with a spectrum of psychiatric symptoms. Case Report: We here report a middle-aged man who was brought to the OPD with symptoms of pervasive irritability and disinhibited behavior for three months, along with complaints of increased activity, reduced sleep, and appetite and was suspicious about his wife, family members and neighbors. The patient had frequent episodes of headache in the past 3 months associated with nausea and restlessness, for which neuroimaging was advised, which showed a hyper-dense lesion in the third ventricle. The patient was referred to neurosurgery and was operated on for the same. Post-operatively, family members reported improvement in his behavior. Conclusion: A detailed systemic evaluation for any organic causes or atypical picture of psychiatric conditions is of extreme necessity. There is a dire need for the liaison of psychiatrists with neuro physicians and neurosurgeons to improve patients in both physical and psychological aspects, especially in psychiatric diagnosis with organic causes.
Keywords: neurosurgery